Dynamic interactions among the industrial sector and its determinants in Jordan - Nawaf Abuoliem; Safwan Mohd Nor; Muhamad Safiih Lola; Ali Matar (Investment Management & Financial Innovations, 2019)
The industrial sector is one of the most vital sectors in the national economy, so different local and global factors affect its performance. The study examines the impact of the global and local macroeconomic variables on the industrial index of the Amman Stock Exchange. This study covered the period from January 2007 to December 2016, which is considered as a crucial period in the Middle Eastern countries. This period encompasses the worldwide economic meltdown from 2007 to 2008, the Arab spring of 2010 and the wars in Syria and Iraq from 2012 to 2014. The macroeconomic variables used in this study as domestic variables from Jordan were the deposit interest rate (IN), inflation rate (INF), money supply 2 (MS2), trade balance (TR), producer price index (PPI) and the industrial production index (IPI). At the same time the global oil price (WTI) was used as a global factor to measure the external shocks. This study used the ARDL bound testing approach to examine the co-integration, short-run and long-run relationships. Moreover, Granger causality test was used to detect the causality relationship in the short and long run between the selected macroeconomic indicators and the industrial index. It was found out that the inflation rate positively influenced the industrial index, which provides some evidence that the industrial sector in Jordan acts as a hedge against inflation. In addition, the global oil price showed a significant negative impact on the industrial sector. Some important implications for investors, government bodies, and policymakers are discussed.